THE PHENOMENON OF FOOD CREATION BUSINESSES WITH CITY’S NAMES AS SOUVENIRS - Anik Nuryani; Handayani Rahayuningsih (Jurnal Bisnis Terapan, 2018)
This research studies the challenge of traditional culinary in the form of new food creation from some cities in Indonesia which claim themselves as special souvenirs and put the city’s name in naming the food. As souvenirs differentiation, it is a good news. However, these food creations are neither the traditional food from the cities nor using local ingredients for the materials. This research studies 3 food creations namely Jogja Scrummy, Malang Strudel and Surabaya Snowcake. Then, it questions the origin of the food creation, the reason of putting the city’s name, and the response of the tourists. The methods used in the research are observation, interview and documentation. The data were analyzed by descriptive qualitative technique. The results show that the food creations claim as special souvenirs to the city as they can not be found in other cities. However, they fulfill the characteristics of souvenirs. Therefore, as the time goes by, these food creations will be recognized as typical souvenirs of the city.